2016
DOI: 10.1038/srep22824
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical oscillations enhance gene delivery into suspended cells

Abstract: Suspended cells are difficult to be transfected by common biochemical methods which require cell attachment to a substrate. Mechanical oscillations of suspended cells at certain frequencies are found to result in significant increase in membrane permeability and potency for delivery of nano-particles and genetic materials into the cells. Nanomaterials including siRNAs are found to penetrate into suspended cells after subjecting to short-time mechanical oscillations, which would otherwise not affect the viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Transfection is the process of introducing plasmid nucleic acid (DNA that carries a gene of interest or mRNA) into target cells that then eventually express the desired nucleic acid or protein. There are a number of strategies for introducing nucleic acids into cells that use various biological, chemical, and physical methods [ 1 – 3 ]. However, there is a wide variation with respect to transfection efficiency, cell toxicity, the level of gene expression, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Transfection is the process of introducing plasmid nucleic acid (DNA that carries a gene of interest or mRNA) into target cells that then eventually express the desired nucleic acid or protein. There are a number of strategies for introducing nucleic acids into cells that use various biological, chemical, and physical methods [ 1 – 3 ]. However, there is a wide variation with respect to transfection efficiency, cell toxicity, the level of gene expression, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, one study showed that Jurkat and MT‐4 T cells have significantly lower levels of HSPGs (~100‐fold) than adherent HeLa and GHOST cells 15 . In addition to cell adhesion, the negative charge of HSPGs also assists in the initial electrostatic binding of some gene delivery vehicles (e.g., cationic polymers and lipids), while specific interactions between HSPGs and viral proteins also promotes viral transduction 13,16 . Indeed, fluorescent imaging has revealed co‐localization of HSPGs with polyplexes in BS‐C‐1 cells 17,18 and blocking HSPGs with dextran sulfate has been shown to reduce the infectivity of HTLV‐1 19 .…”
Section: Relevant Aspects Of T Cell Biologymentioning
confidence: 99%
“…The trapped bead “ drilling ” frequency is indicated as 1 Hz. In [138] mechanical shaking at 10-800 Hz was effective at increasing molecular and nanoparticle uptake, with a frequency of 100 Hz being particularly effective towards this goal. This is to be connected with the ~kHz oscillations in trap´s stiffness reported by Mondal et al with their fs pulsed trap [131].…”
Section: Mechanical Damage In Optical Tweezersmentioning
confidence: 99%
“…This “ pulsing ” approach indeed reduces the thermal mode but thermomechanical processes are more readily induced (see Section 4). Then, caution is advised to check for possible thermoacoustic effects on the sample, especially at 100–1000 Hz frequencies [138].…”
Section: Strategies To Avoid Damage In Optical Tweezersmentioning
confidence: 99%